(3MGTjI ejQ CHh GdaJM Ydi GdBOGH GdYVOjIs - (3GdSYjOj, GdCQOHjdj, eMeO Hf Cejf, cGf MjG (B875 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi GagGe GdNWGH hHYO agPg aGFOI YLGH Ydi GdTQM GdeTghQ Hjf Ghdi GdCdHGH ddQSGdI GdYVOjI aj GdBOGHs
(3BNQgG (B:s
(3ceG jLQj aj UhQI YOe GdJbjjO cPdc jLQj aj UhQI GdJbjjO HCf jbGd Ef CQOJ Hbhdcs
(3GdNWhW eNJdags
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2/142s
(3gOjI GdYGQajf (B2 / 207s
(3EjVGM Gdecfhf (B1 / 41s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs